I'm Skinny, I'm Worth More: Fashion Models' Experiences of Aesthetic Labor and Its Impact on Body Image and Eating Behaviors. (January 2023) - Fixsen, Alison; Kossewska, Magdalena; Bardey, Aurore
The fashion industry has been critiqued for promoting ultra-thin bodies, yet the relationship between models' aesthetic labor and eating disorder (ED) development is unclear. Using interpretive phenomenological analysis, we explored the lived experiences of nine female fashion models including metaphors they used to describe body perceptions and eating behaviors. Four superordinate themes emerged: Shaped for the industry; The body as a market product; Food restriction ("it's almost glamorized"); Toward a healthier modelhood. Models' career trajectories were those of lost childhoods, punitive body rules, inadequate dietary advice, and self-regulated food restriction. Models were "shaped" by agents from an early age to conform to the industry's body rules irrespective of the physiological and psychological consequences. A "toxic" side to this aesthetic industry was depicted; agents were judged callous and money-focused, while idioms like, "feeling like a piece of meat" and "being a hanger of clothes" conveyed a deep sense of degradation and objectification. Ideas instilled at a formative age continued to influence self-image and eating patterns into maturity, pointing to an industrial element to the construction of eating disorders. Our study highlights how infantilization, sexism, and other unethical elements become normalized in poorly regulated industries such as fashion, with dire consequences for the health and wellbeing of employees. Model agencies should recognize the impact of occupational edicts and poor communication on young recruits in a sensitive phase of personality development. Finally, we advocate for more acknowledgment and further investigation into eating disorder construction commercial/industrial side.